Experimental evolution shows Drosophila melanogaster resistance to a microsporidian pathogen has fitness costs. - Vijendravarma, R; Kraaijeveld, A; Godfray, H (2009)
Most organisms experience strong selection to develop mechanisms to resist or tolerate their pathogens or parasites. Limits to adaptation are set by correlated responses to selection, for example reduced abilities to detect other parasites or trade-offs with other fitness components. For a few model systems it is now becoming possible to compare the evolutionary response to a broad range of natural enemies. In Drosophila, the evolutionary responses to ectoparasitic mites, parasitoids, and fungal and bacterial pathogens have previously been studied. Here replicate lines of D. melanogaster were exposed to the microsporidian parasite Tubulinosema kingi over a period of 61 weeks, with overlapping generations. Compared to controls, exposed lines had higher early-life fecundity and increased longevity when infected suggesting successful selection for resistance or tolerance. In the absence of the pathogen, exposed lines had lower fecundity when reared under harsh environmental conditions, and were poorer larval competitors than controls. They also had relatively higher densities of haemocytes, a component of the cellular immune system. Defense against this pathogen resembles more that against macroparasites than microsparasites, and this is interpreted in the light of what is known about the mechanisms of resistance to microsporidians.